Navigating Heritage: Challenges and Strategies for Oral Tradition Preservation in Jalawastu Community, Central Java, Indonesia - Akhiroh, Ninuk Sholikhah; Alimi, Moh. Yasir; Marbun, Ririn Natasha; Harinda, Vania Aurellia; Wibisono, Muhammad Syahrial (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2025)
Globalisation and modernisation are often perceived as threats to preserving cultural traditions. This study explores how the Jalawastu community in Brebes, Central Java, Indonesia, maintains its cultural identity through practising and transmitting oral traditions. Despite exposure to external influences—including interpersonal interactions and digital communication technologies—the Jalawastu people demonstrate a dynamic between adaptation and cultural continuity. Their exposure to the outside world, facilitated by interpersonal interactions and communication technologies, has had significant implications for the continuity and transformation of their oral traditions. Using a qualitative research design, data were gathered through observation, interviews, and documentation. The analysis draws on oral tradition and social change theories, particularly Ogburn’s (1922) and Soekanto’s (2012) works. The findings reveal a complex interplay between cultural preservation and transformation. Oral traditions are being preserved through their integration into cultural tourism, while shifts occur due to increased interaction with outsiders, especially through employment and intermarriage. These changes have prompted younger generations to leave the village, often due to their inability to conform to traditional norms. The study offers valuable insights for cultural policy, community development, and heritage education programs, particularly in rural and indigenous settings facing similar challenges.